2021
DOI: 10.1111/odi.13790
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of topical administration for oral lichen planus: A network meta‐analysis

Abstract: Objective: To examine the comparative efficacy and safety of topical administration for oral lichen planus. Materials and Methods: An electronic database search (1st January 1946 to 1st May 2020) for randomised controlled trials identified 34 studies involving eight interventions (clobetasol, betamethasone, triamcinolone, dexamethasone, fluocinolone, tacrolimus, pimecrolimus, and cyclosporine); these studies were subjected to network meta-analysis using direct and indirect comparisons [efficacy indicators: cli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(20 citation statements)
references
References 65 publications
(150 reference statements)
0
20
0
Order By: Relevance
“…Importantly, the inclusion criteria of previous reviews were different from our review. Some reviews 33,34,36,38 included trials with only clinical diagnoses or enrolling participants without symptoms. Some reviews 10,13,36 only selected studies published in English, which may imply a loss of information only available in other languages.…”
Section: Relapsementioning
confidence: 99%
“…Importantly, the inclusion criteria of previous reviews were different from our review. Some reviews 33,34,36,38 included trials with only clinical diagnoses or enrolling participants without symptoms. Some reviews 10,13,36 only selected studies published in English, which may imply a loss of information only available in other languages.…”
Section: Relapsementioning
confidence: 99%
“…The study conducted by Ni Riordain et al [11] in a cohort of 100 English patients (30 men and 70 women) identified a direct annual cost of £ 398.58 (€ 541.16) per patient, which greatly differs from the identified annual costs in our study (annual cost per person of 1087.2 € per person). Ni Riordain et al also stratified the costs in relation to the severity of the disease based on the therapeutic protocol (only local or combined with systemic therapy), reporting a higher cost for patients who needed systemic therapy (£ 663 (€ 900.16) vs. £ 301 (€ Table 2 Summary of annual direct costs of OLP stratified according to nationality, therapy, and clinical forms 1 Statistically significant difference between therapy and no therapy groups in overall patients-ANOVA p < 0.05 2 Statistically significant difference between clinical forms in overall patients-ANOVA p < 0.05 3 Statistically significant difference between overall Italian patients and Finnish patients-ANOVA p < 0.05 4 Statistically significant difference between therapy and no therapy groups in Italian patients-ANOVA p < 0.05 5 Statistically significant difference between clinical forms in Italian patients-ANOVA p < 0.05 6 Statistically significant difference between therapy and no therapy groups in Finnish patients-ANOVA p < 0.05 7 Statistically significant difference between clinical forms in Finnish patients-ANOVA p < 0.05 Abbreviations: OLP, oral lichen planus; n, number Annual visit cost (€) 1,2,3 Annual swab cost (€) 1,2,3,6 Annual biopsy cost (€) 4 Annual drug cost (€) 1,2,3,4,5,6,7 Total annual cost (€) The important cost difference compared to our study (average of € 541 vs. € 1087) must take into account some methodological differences: first, the study by Ni Riordain et al [11] was conducted by administering questionnaires, primarily aimed at identifying the number of examinations, by oral medicine doctors and by GPs, directly to patients, and any drugs prescribed for the treatment of OLP during the last 12 months. The study did not analyze the medical records, which should be more realistic than a questionnaire (recall bias).…”
Section: Discussionmentioning
confidence: 99%
“…The chronic course of this disease, associated with a wide spectrum of clinical manifestations and symptoms, and the risk of malignant transformation require careful and meticulous management of this condition and regular follow-up. Specifically, as OLP is considered an immune-based disease that mimics a type IV hypersensitivity reaction, the main therapeutic regimen consists of local immunosuppressive drugs, mainly corticosteroids, generally administered in symptomatic patients or when inflammation is widespread [7]. These are primarily used topically, but also systemically in the most severe cases, requiring careful control of the onset of possible side effects (e.g., candidiasis, hirsutism, hypertension, hyperglycemia, Cushing's syndrome); nevertheless, some patients do not improve with conventional local immunosuppressive therapy (non-responders) and need secondary-line therapy [8].…”
Section: Introductionmentioning
confidence: 99%
“…The successful management of OLP remains challenging ( 7 - 14 ). A complete cure is not currently a realistic goal because of its recalcitrant nature.…”
Section: Introductionmentioning
confidence: 99%